Exploratory study of sensitization in ferritic stainless steel welds produced via cryogenic cooling - Amuda, Muhammed Olawale Hakeem; Mridha, Shahjahan (2011)
Enhanced weld cooling via forced convection using cryogenic cooling technique is an option for controlling grain growth in the HAZ of ferritic stainless steel and hence improves weld ductility. However, this technique probably alters the martensite distribution in the high-temperature heat affected zone (HTHAZ) which is a critical constituent in analyzing susceptibility to sensitization in ferritic stainless steel grades. In the present work, forced convection weld cooling of AISI 430 ferritic stainless steel weld using cryogenic liquid is undertaken and the effect on sensitization is reported. The study indicates that cryogenic cooling increases the cooling rate in the HTHAZ and reduces the martensite volume percent by an average of 20%. This reduction in martensite content in the HTHAZ increases the level of ditched structure in cryogenic-treated welds. There are more ferrite-martensite ditched grain boundaries in cryo-treated welds than are in conventional welds. Though, the cryo-treated welds exhibit greater ditched boundary, the structure is still acceptable since no single grain boundary is completely surrounded by ditches.